The influence of green fashion products on the achievement of the 12 Sustainable Development Goals for masters and doctoral students - Valenga, Ana Carolina Velozo; Stefani, Silvio Roberto; Carvalho, Luísa Margarida Cagica; Chiusoli, Claudio Luiz (Revista de Administração da UFSM, 2023)
Objective: Agenda 2030 encourages sustainable production and consumption through the SDG 12. In this case, the objective of the present study was to analyze how masters and doctoral students consume fashion products, what their conception about products of the circular economy and how this behavior can contribute to the reach of the SDG 12. Metodology: This is a descriptive and quantitative research with a data collection instrument based on questionnaires, examined using the non-parametric chi-square test to verify the existence of a relationship between the variables according to gender. Discoveries: Identified that the lack of knowledge of society and students about the subject and price of green products is the main challenge the CE faces. In addition, the reduction of pollution and waste was pointed out by the participants as one of the main influencers in the green products consumption. Regarding the knowledge of Agenda 2030 and SDGs, 91.18% demonstrated knowledge. 37.3% of the respondents are not willing to pay more for the purchase of green products. Research implications: This study contributes to the literature by extending information on sustainability and consumption and SDG12 in IHE students, focusing specifically on masters and doctoral students. Practical implications: Studies on perceptions and practices of green product consumption is important and can contribute to the awareness of higher education students and contribute to the achievement of the SDG12. Originality: This is an innovative study that can serve as a research agenda model for other IHEs and contribute to Agenda 2030 SDG12.